2020
DOI: 10.1016/j.heliyon.2020.e04226
|View full text |Cite
|
Sign up to set email alerts
|

Mild head trauma in elderly patients: experience of an emergency department

Abstract: Introduction We evaluated the risk profile of elderly patients who came to the emergency department for mild head trauma. The primary goal was to determine the difference in the incidence of posttraumatic intracranial hemorrhage (ICH) after minor head injury (MHI). The secondary objective was to assess worse outcome, such as: hospitalization rate, rate of re-admission, need of neurosurgery. We also assess the admission process times and length of hospital stay. The ultimate goal was to optimize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
0
19
0
3
Order By: Relevance
“…Recent studies have increasingly focused on the lasting effects of MHI and observed that chronic diseases were associated with post-discharge mortality after MHI. It has been argued that its effect on older patients could be partly explained by pre-existing comorbidities [ 50 , 52 , 55 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. It may be interesting for future studies to assess the possible impact of anticoagulant drugs on long-term mortality, and also the effects that DOACs may have on the overall outcome of emergency and elective neurosurgical pathologies, as raised by our group [ 48 , 53 , 58 , 91 , 92 , 93 , 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have increasingly focused on the lasting effects of MHI and observed that chronic diseases were associated with post-discharge mortality after MHI. It has been argued that its effect on older patients could be partly explained by pre-existing comorbidities [ 50 , 52 , 55 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. It may be interesting for future studies to assess the possible impact of anticoagulant drugs on long-term mortality, and also the effects that DOACs may have on the overall outcome of emergency and elective neurosurgical pathologies, as raised by our group [ 48 , 53 , 58 , 91 , 92 , 93 , 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the changes of fibrinolysis inhibitors, few cases have been reported. Concerning platelet function, patients with TBI appear to have moderately low counts, but often, they are activated, permitting pro-coagulant activity [ 25 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…In addition to the aforementioned factors, the severity of coagulation disorders is influenced by environmental factors and the resulting therapeutic factors such as the genetic background, inflammation, and premedication, especially with oral anticoagulant use [ 101 , 102 , 103 ]. Concerning the involvement of anatomical regions, associations were found between TIC and the involvement of the abdominal region [ 93 , 101 , 102 , 103 ]. A recent study reported that a higher number of involved regions was correlated with the early development of TIC [ 93 ].…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The tendency to bleed is more pronounced with age [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Since 2015, antiplatelets have increasingly been used as the primary method of preventing cardiovascular diseases [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%